Ewangelicy w okolicy Szadku i Zduńskiej Woli w XIX-XX w. - Stulczewski, Jarosław (Biuletyn Szadkowski, 2009)
The first Protestants, who came from Czechia and Saxonia, settled in the region of Szadek and Zduńska Wola at the turn of the 18th century. An Evangelical-Augsburg Church parish was established in Zduńska Wola in 1827. In the 1820s fourty Protestant families resident in Szadek succeeded in taking over the Holy Spirit church building. As the number of migrants from Germany increased and the community of Protestant residents grew, new facilities and institutions serving their needs came into being. Chapels and cemeteries in Zduńska Wola, Szadek and Łobodzice started functioning in the first half of the 19th century. The most outstanding among the clergy men who were actively engaged in the life of the Evangelical community was Edward Boerner, who held the office of parson in 1856–1910. In the interwar period the largest Protestant communities near Szadek, apart from Zduńska Wola, were Łobudzice, Annopole, Izabelów, Pratków i Zborowskie. World War II and the post-war period brought displacements of German population and disappearance of the heritage of the Evangelical community in this region.